GSA: operacionalizando a gamificação em atividades do processo de desenvolvimento de software - Porto, Daniel de Paula (2021)
Context: Software development companies are constantly seeking practices that improve the execution of their activities and, consequently, their processes. Several initiatives for using gamification have been observed in different areas, providing evidence on different types of activities. However, the implantation of gamification in a real software development environment requires planning and systematization in order to make this alternative effective and efficient. This fact became clear after we performed a systematic mapping of the literature, in which analyzed the initiatives to use gamification, with special attention in the area of Software Engineering. Objective: Establishing a systematic way of applying gamification to activities of the software development process to improve and make more effective activities that need to be improved, with the objective of improving the process as a whole. Method: A systematic mapping was carried out to analyze gamification use initiatives and, concerning Software Engineering activities, some frameworks have identified, but also difficulty in using them. Thus, based on what we found, it has been defined the GSA framework and a strategy of how to apply gamification in software engineering activities. They were defined in an evolutionary way, based on action research. During the cycles of evolution, three experimental studies were carried out, being them a pilot study and two case studies in a real software development company. Such studies allowed us to improve both the framework and the strategy. Results: The results of the studies have shown improvement in carrying out the selected Software Engineering activities with gamification. In the case of the “Timesheet fill” activity, a decrease in more than 75% in the time of filling out the Timesheet was observed. In the case of the “Requirements Reading and Review” activity, we noticed a decrease of at least 68% in the number of defects, when compared with a historical basis of the company, by applying the framework and the strategy to Requirements Reading and Review Activities. Conclusion: The use of a framework and a strategy to deploy gamification in Software Engineering activities contributed to the improvement in the execution of activities that were considered problematic in the context of the company’s software development process, and hence may contribute to the process as a whole.